Od funkcjonalnego mieszkania ku zrównoważonej przestrzeni zamieszkiwania – rola infrastruktury osadniczej - Cesarski, Maciej (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
This study is focused on the importance of housing and other settlement infrastructure for the sustainable development of the inhabited areas and the whole living space on the Earth’s surface. Development of the settlement infrastructure, based in technical and constructional terms on flat, may serve well the sustainable development of these spaces. Application of the method signaled in this study for the transformation of economic activities in order to approximate them, through the concept of settlement infrastructure, to the chief social values of sustainable development of living space, including inhabited space, requires a real shift in the paradigm of economic growth to the paradigm of sustainable development